«THE CAPITAL FLIGHT» CHALLENGES FOR CHINA’S ECONOMY - B. Loguinov (Вестник университета, 2017)
In the article the analysis of «the capital flight» from China’s economy is made. The level of offshorization of this country is assessed. The author also enumerated forms of illicit capital investment abroad from the territory of China. As pointed out in the article, there are offshores which are chosen by the residents of China’s economy.